New cyanide-free alkaline electrolyte for the electrodeposition of Cu-Zn alloys using glutamate as complexing agent - Pary, Paola (2019)
Glutamate is a potential replacement of cyanide in alkaline electrolytes due to its capability to form complexes with bivalent metal ions. Since promising results were achieved with copper and zinc plating baths, and the use of cyanide implies environmental and safety disadvantages, it was decided to study the possibility of codepositing these two metals using sodium glutamate as complexing agent. Electrochemical processes involved in electrodeposition of copper and zinc individually as well as in solutions containing both metal ions were studied utilising cyclic voltammetry. Cu-Zn deposits obtained at different current densities from solutions of different composition were characterized by SEM and EDS. It was concluded that the system has a normal behavior, according to Brenner’s classification, since the more noble metal is deposited preferentially. The plating bath containing 30% molar of Cu2+ was selected to continue the studies of the system.